Indigenous Cultural Heritage: Developing New Approaches and Best Practices for World Heritage Based on Indigenous Perspectives and Values - Diane Archibald (Protection of Cultural Heritage, 2020)
In support of advancing the recognition and inclusion of Indigenous Cultural Heritage in all its diverse forms within the UNESCO World Heritage Convention and World Heritage Site designations, this paper documents and discusses the presentations, Indigenous-led Forum, and recommendations and outcomes of the International Conference on Indigenous Cultural Heritage organized by the ICOMOS International Scientific Committee on Theory and Philosophy of Restoration and Conservation in partnership with the First Nations House of Learning, University of British Columbia, Vancouver, Canada, in November 2019.